ANALISIS DAMPAK PAJAK PENGHASILAN (PPH) TERHADAP SUBJEK DAN OBJEK PAJAK PENGHASILAN DALAM KONTEKS PERPAJAKAN - Siska Permata Sari Hrahap; Thasya Virdinia; Husnul Khotima; Panisa Panisa; Dini Vientiany (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This article discusses the impact of Income Tax (PPh) on Tax Subjects and Tax Objects in the context of taxation. PPh is a tax obligation imposed on income received or earned by the tax subject in the tax year. Tax subjects can be individuals, business entities, or other legal entities that earn income. The tax object is income which is the basis for being subject to PPh. The author acknowledges that there are shortcomings in the preparation of this article and hopes for input for future improvements. It is hoped that this article can contribute to understanding the basics of taxation, increase awareness of the importance of paying taxes, and increase efficiency in the tax administration system.